Acoustic Coatings—A Discreet Way to Control Acoustic Environment - Cucharero, Jose; Hänninen, Tuomas; Makkonen, Marko; Lokki, Tapio (Frontiers in Built Environment, 2021)
Acoustic comfort is directly related to enhanced well-being and performance of people. Typical challenge faced by architects and acousticians is to achieve adequate acoustics while maintaining the aesthetics of the space and reducing the visual aspects of acoustic materials and elements. In this paper we present a biofibre-based acoustic coating as a feasible solution to improve acoustic environments while preserving the aesthetics of spaces. The acoustic coating is a thin layer of absorption material, but the coating can be sprayed on other sound absorbing structures to make it more effective on wide frequency range. In addition, this biofibre-based acoustic acts as a carbon sink during its operating life, thus reducing the carbon footprint of the building. Therefore, the coating is sustainable and environmental friendly solution. The absorption properties of the biofibre-based coating is demonstrated here with three case studies which all had demanding requirements to conceal the acoustic structures.